Epidemiological profile of the healthcare-associated infections in an Intensive Care Unit from 2019 to 2020 (Research, Society and Development, 2021)
Introduction: Healthcare-associated infections (HAI) are a severe problem to the healthcare worldwide, raising internment costs e mortality rates. Therefore, the need for monitoring and evaluation of incidence density and epidemiological profile of the HAI occurred in the Hospital Universitário de Sergipe (HU-UFS) grows. Objective: To evaluate if there is a significant difference between incidence/prevalence of HAI on patients admitted to the intensive care unit (ICU) in association with predisposing factors. Methodology: This study was realized with bibliographic research and data survey from the epidemiological vigilance records made by the service of hospital infections control of the patients admitted to the ICU from 2019 to 2020. Patients who meet the criteria for a minimum stay of 24 hours in the unit are included, and those who do not meet this criterion are excluded. Results: There has been a higher density of HAI in the third trimester of 2020, with 26,44. As for invasive devices, it was observed a higher rate of venous central line in the fourth trimester of 2020, with 83,9, but there was not elevation of HAI in this site. It was also observed a higher frequency of ventilator-associated pneumonia (VAP), within the topographies, corresponding to 47,22% of all cases. Conclusion: The rates found in this study are in consonance with the numbers published by Anvisa about other institutions with the same profile.